A Preliminary Note on the Occurrence of Copepods under Sea Ice near Syowa Station,Antarctica - Fukuchi, Mitsuo; Tanimura, Atsushi (1981)
P(論文) Net samplings of zooplankton were done in the ice-covered sea area near Syowa Station (69°00'S, 39°35'E), Antarctica, during the summer, autumn and spring seasons in 1970 and 1975. Copepods were the main constituents of the zooplankton community. Ctenocalanus vanus, Stephus longipes, Paralabidocera antarctica, Oithona similis, Oithonafrigida, Oncaea curvata and Harpacticoid copepods were identified. Among them, while unidentified copepod nauplii were numerously distributed, O. similis and O. curvata occurred dominantly during late summer, autumn and spring. P. antarctica and O.frigida occurred in small numbers in summer. Species composition of copepods changed seasonally. departmental bulletin paper